2022
DOI: 10.1111/hiv.13394
|View full text |Cite
|
Sign up to set email alerts
|

Re‐assessing the late HIV diagnosis surveillance definition in the era of increased and frequent testing

Abstract: Objectives Late HIV diagnosis (CD4<350 cells/mm 3 ) is a key public health metric. In an era of more frequent testing there is greater likelihood of HIV diagnosis occurring during seroconversion, when CD4 counts may dip below 350. We apply a correction, considering markers of recent infection and reassess one-year mortality following late diagnosis. Methods We used national epidemiological and laboratory surveillance data on all persons diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…This showed that roughly 75% of late diagnoses in 2020 were actually diagnosed ‘very late’ with a CD4 count <200 cells/mm 3 . This includes people who are hospitalized with opportunistic infections, some with CD4 counts <50 copies/mL [7, 8].…”
Section: Definitions Of Late and Very Late Diagnosismentioning
confidence: 99%
“…This showed that roughly 75% of late diagnoses in 2020 were actually diagnosed ‘very late’ with a CD4 count <200 cells/mm 3 . This includes people who are hospitalized with opportunistic infections, some with CD4 counts <50 copies/mL [7, 8].…”
Section: Definitions Of Late and Very Late Diagnosismentioning
confidence: 99%
“…It is also known that most people who are seroconverting recover their CD4 count within a year [ 13 ], typically within 6 months, and those who do not could rather be considered as ‘fast progressors’ [ 6 , 14 , 15 ]. Furthermore, research from the UK and Sweden shows that among people newly diagnosed with HIV with a negative test recorded, the vast majority had their last negative test within the last 12 months, so lengthening the cut‐off would have minimal effect [ 9 , 16 ]. The 12‐month cut‐off was endorsed by members of the EACS Governing Board and antiretroviral therapy (ART) panel group.…”
Section: Resultsmentioning
confidence: 99%
“…The EuroTEST Initiative convened a working group of experts in HIV from Europe, including clinicians, epidemiologists, public health professionals and civil society, to review the existing late HIV diagnosis definition in January 2022. Multiple meetings were held for stakeholders to discuss possible updates to the definition based on previous research [ 7 , 8 , 9 ]. The full list of experts consulted can be found in Appendix S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion of recent infections from population‐ level analyses allowed researchers to correct the total number of late‐diagnosed cases to obtain more precise data. Such reclassification was successfully applied in the study by Kirwan et al, and allowed the calculated late diagnosis rate to be decreased by the overall factor of 14% [9]. The correction rates accounting for recent infection were highest among extensively tested populations (e.g.…”
mentioning
confidence: 99%